Using human, social, structural, and positive psychological capital to explore science and mathematics teacher retention - Adem Ekmekci; Mahtob Aqazade; Rebecca McGraw; Gregory Rushton; David J. Gibson; Cathleen Cerosaletti; Michael Daley; Burak Kucuk (International Journal of STEM Education, 2025)
Abstract Background Teacher turnover is a dire and chronic problem for many education systems across the globe. According to UNESCO, 70% of teachers will be replaced by 2030. This study investigates the relationship between the retention of science and mathematics teachers and factors related to human, social, structural, and positive psychological capital—a four-capital teacher retention model. More specifically, this study explores how teaching self-efficacy, leadership engagement, teacher-school fit, diversity beliefs, community connections, and professional social network characteristics (e.g., size, bridging, proximity, reach) relate to teacher retention. Additionally, potential differences in retention and the aforementioned factors related to the four-capital model between Master Teaching Fellows (MTFs) and their peers (non-MTFs) with similar human capital (demographics and experience) are explored in this study. Participants were K-12 science and mathematics teachers (85 MTFs and 82 non-MTFs) from six different regions across the U.S. MTFs participated in one of seven long-term (5–6 years) Robert Noyce Master Teaching Fellowship Programs funded by the National Science Foundation. Results Leadership engagement was positively associated with shifting (from teaching to a formal leadership position). Teacher-school fit was negatively associated with leaving. For secondary teachers, teaching self-efficacy was positively associated with shifting to a leadership position. Leadership network size, bridging, and geographic proximity variables were positively related to shifting when compared to staying as classroom teachers. Teaching network bridging and leadership network bridging were positively related to leavers when compared to stayers. MTF shifters were likely to shift earlier in their careers than non-MTFs. Lastly, MTFs had higher self-efficacy, geographically larger teaching networks and leadership networks, and more contacts and bridging roles in their leadership networks than non-MTFs. Conclusion Findings provide support for teacher leadership programs in promoting leadership roles and responsibilities for STEM teachers and retaining teachers in STEM education either in the classroom or in administrative roles. These findings suggest that school administrators may also play a key role in encouraging teachers to engage in leadership activities and have a broader impact on public education by, for example, adopting a hybrid model of leadership roles that involves classroom teaching.